2016
DOI: 10.3892/mmr.2016.5314
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α enhances vascular cell adhesion molecule-1 expression in human bone marrow mesenchymal stem cells via the NF-κB, ERK and JNK signaling pathways

Abstract: The migration of circulating mesenchymal stem cells (MSCs) to injured tissue is an important step in tissue regeneration and requires adhesion to the microvascular endothelium. The current study investigated the underlying mechanism of MSC adhesion to endothelial cells during inflammation. In in vitro MSC culture, tumor necrosis factor-α (TNF-α) increased the level of vascular cell adhesion molecule-1 (VCAM-1) expression in a dose-dependent manner. The nuclear factor-κB (NF-κB), extracellular signal-regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 25 publications
(25 reference statements)
4
24
0
1
Order By: Relevance
“…TNF-a has been reported to increase the relative protein levels for phosphorylated p38, JNK and ERK 1/2 in many cell types. [38][39][40][41] Using a porcine model of intestinal ischemia, Shifflett et al demonstrated that inhibition of JNK resulted in enhanced recovery of barrier function, whereas inhibition of ERK1/2 and p38 MAPK had a deleterious effect on mucosal recovery from ischemia. 37 The JNK and p38 cascades are activated by inflammatory cytokines and a wide variety of cellular stresses.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a has been reported to increase the relative protein levels for phosphorylated p38, JNK and ERK 1/2 in many cell types. [38][39][40][41] Using a porcine model of intestinal ischemia, Shifflett et al demonstrated that inhibition of JNK resulted in enhanced recovery of barrier function, whereas inhibition of ERK1/2 and p38 MAPK had a deleterious effect on mucosal recovery from ischemia. 37 The JNK and p38 cascades are activated by inflammatory cytokines and a wide variety of cellular stresses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 , 4 ] Tumor necrosis factor-alpha (TNF-α) is one of cytokines involved in systemic inflammation, which could alter leukocyte adhesion molecule expression on cultured endothelial cells such as human umbilical vein endothelial cells (HUVECs). [ 5 ] Cellular adhesion molecule responding to pathophysiological stimuli can influence the progress of atherosclerosis by mediating the interaction between blood cells (such as leukocytes) and endothelial cells. [ 6 , 7 ] Inflammation could be promoted by TNF-α via upregulating expression of adhesion molecules, such as intercellular cell adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1), and E-selectin.…”
Section: Introductionmentioning
confidence: 99%
“…This provides a proof of principle that the inflammatory environment impacts on the parameters investigated in the current settings. However, while corresponding to the experimental design in several previous studies [ 39 , 40 , 41 , 42 ], these high cytokine concentrations are artificial and unlikely to be found in vivo. Therefore, we also used the same cytokines at low concentrations (0.01 ng/mL for IL-1β and 0.1 ng/mL for TNF-α).…”
Section: Discussionmentioning
confidence: 99%